Polish electronics in high energy physics & aerospace technology - Jankowski, Mariusz; Makowski, Dariusz; Cichalewski, Wojciech; Napieralski, Andrzej (Photonics Letters of Poland, 2016)
Department of Microelectronics and Computer Science of Lodz University of Technology has high expertise in the field of design of electronic and microelectronic systems for wide range of applications. DMCS design teams participated in large number of national and international scientific research programs, grants and commercial contracts. Many of these works resulted in an introduction of new systems into scientific installations or putting new product into general markets. The paper presents selected works focused on aspects of research on accelerator control systems for high energy physics, nuclear fusion based new energy sources and design of integrated electronics for space applications. Full Text: PDF References http://tesla.desy.de DirectLink D. Makowski, et al., Solid state neutron detector system, Germany, Switzerland, France, European Patent Office, Patent no 05011654.0-1240, EP20050011654. DirectLink W. Giergusiewicz, W. Jalmuzna, K. Pozniak, N. Ignashin, M. Grecki, et al., Low latency control board for LLRF system: SIMCON 3.1, Proc. SPIE 5948, Photonics Applications in Industry and Research (2005). CrossRef D. Makowski, A. Mielczarek, P. Perek, A. Napieralski, L. Butkowski, J. Branlard, M. Fenner, H. Schlarb, and B. Yang, High-Speed Data Processing Module for LLRF, IEEE TRANSACTIONS ON NUCLEAR SCIENCE, VOL. 62, NO. 3, JUNE (2015). CrossRef K. Przygoda, T. Poźniak, A. Piotrowski, D. Makowski, G. Jabłoński, A. Napieralski, Prototype Control System for Compensation of Superconducting Cavities Detuning Using Piezoelectric Actuators, IEEE Transactions on Nuclear Science, vol. 56, no. 4, pp.2336–2340, Aug. (2009). CrossRef D. Makowski, et al., Interfaces and Communication Protocols in ATCA-Based LLRF Control Systems, IEEE Transactions on Nuclear Science, vol.56, no.5, pp.2814-2820, Oct. (2009). CrossRef D. Makowski, et al., Prototype Real-Time ATCA-Based LLRF Control System, IEEE Transactions on Nuclear Science, vol. 58, no. 4, pp. 1553–1561, Aug. (2011). CrossRef D. Makowski, et al., High-Performance Image Acquisition and Processing System with MicroTCA.4, IEEE Transactions on Nuclear Science, vol. 62, no. 3, pp. 925–931, June (2015). CrossRef G. Jabłoński, et al., IEEE 1588 Time Synchronization Board in MTCA.4 Form Factor, IEEE Transactions on Nuclear Science, vol. 62, no. 3, pp. 919–924, June (2015). CrossRef S. Simrock, at all, Maturity assessment of ITER diagnostics plant instrumentation and control design, Fusion Engineering and Design, pp. 952-956, (2015). CrossRef K. Skup, P. Orleański, W. Nowosielski, M. Jankowski, G. Jabłoński, Ł. Starzak, M. Szermer Michał, A. Napieralski, R. Darakchiev, M. Mroczkowski, Mixed Signal ASIC Controller for Satellite Medium Power DC/DC Converters, Proc. Conf. "Mixed Design of Integrated Circuits and Systems". Poland, Toruń, pp. 359-363, (2015). CrossRef K. R. Skup, P. Grudziński, P. Orleański, Application of Digital Control Techniques for Satellite Medium Power DC –DC Converters, Int. Journal of Electronics and Telecommunications, pp. 77 83, 2011. CrossRef M. Brown, Power Sources and Supplies: World Class Designs, Newnes, (2007). DirectLink M. Santos, C. Pires, J. Guilherme, N. Horta, Overview of Radiation Effects and Design Constraints off Fully Custom SMPS, IEEE Asia Pacific Conference on Circuits and Systems, APCCAS 2008, pp. 372 375, (2008). CrossRef L. Balogh, A Practical Introduction to Digital Power Supply Control, Power Supply Design Seminar 2004/05, (2005). DirectLink